STUDY ON RECENT TRENDS IN CORPORATE REPORTING - Prachi; Singh, Manu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the present study, a comparative study of mental health and educational achievement of secondary level students has been done. For the study, 2 schools have been selected out of 10 secondary schools of district Mathura and 6 points related to mental health have been studied on the basis of gender. 1. Emotional stability, 2. Adjustment. 3. Autonomy, 4. Security-insecurity 5. Self-concept and 6. Intelligence. After analyzing the results, it was found that mental health positively affects the educational achievement of male and female students and no difference was found in the 6 concepts of mental health on the basis of gender.